2021
DOI: 10.1002/adhm.202001987
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Retention Quantification of Supramolecular Hydrogels Engineered for Cardiac Delivery

Abstract: Recent advances in the field of cardiac regeneration show great potential in the use of injectable hydrogels to reduce immediate flush-out of injected factors, thereby increasing the effectiveness of the encapsulated drugs. To establish a relation between cardiac function and retention of the drug-encapsulating hydrogel, a quantitative in vivo imaging method is required. Here, the supramolecular ureido-pyrimidinone modified poly(ethylene glycol) (UPy-PEG) material is developed into a bioactive hydrogel for rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Further elucidation of FSTL1 signaling between CMs and cFBs in the healthy and ischemic heart could provide insights into how we can tap into this intercellular communication to support cardiac repair. As we confirm that FSTL1 acts as a secreted, paracrine factor, clinical translation could be accomplished via various delivery routes to ensure effective local concentrations, for example, by applying an epicardial patch, 20 drug-releasing carriers such as injectable gels, 67 or implantable mini-pumps. 68 Large animal models using clinically applicable methodology 69 seem an appropriate means to further investigate the translational potential of FSTL1 for ischemic heart disease.…”
Section: Discussionmentioning
confidence: 53%
“…Further elucidation of FSTL1 signaling between CMs and cFBs in the healthy and ischemic heart could provide insights into how we can tap into this intercellular communication to support cardiac repair. As we confirm that FSTL1 acts as a secreted, paracrine factor, clinical translation could be accomplished via various delivery routes to ensure effective local concentrations, for example, by applying an epicardial patch, 20 drug-releasing carriers such as injectable gels, 67 or implantable mini-pumps. 68 Large animal models using clinically applicable methodology 69 seem an appropriate means to further investigate the translational potential of FSTL1 for ischemic heart disease.…”
Section: Discussionmentioning
confidence: 53%
“…In our group, we showed a ureido-pyrimidinone-based hydrogel that was labeled with a radioactive tracer ( 111 Indium), traceable in vivo. [133] Here, a small pilot showed the redistribution 4 h after injection in a healthy porcine heart, with 8% of the hydrogel being retained at the inject spot, whereas a high content redistributed to the lungs (29% n = 1, 9.5% n = 2) and bladder and urine (16% n = 1, 22% n = 2). When the hydrogel was modified with a recombinant collagen type-1 based material, cardiac retention was around 16% after 4 h, displaying redistribution of the hydrogel mainly to the lungs (13% n = 1, 19% n = 2), as well as the bladder and urine (10% n = 1, 13% n = 2).…”
Section: Off-target Effectsmentioning
confidence: 74%
“…At low frequency (higher relaxation time), polymer chains start to flow and rearrange, showing liquid-like properties. At high frequency (shorter relaxation time), polymer chains do not have enough time to rearrange and therefore exhibit solid-like properties . Thus, the decreased tan δ of PDA30@CD and PDA50@CD hydrogels with increased frequency indicated that hydrogels had a strong network structure at high frequency .…”
Section: Resultsmentioning
confidence: 99%